Production of spinor condensates of 87Rb released from a magnetic trap - Gartman, Rafał; Piotrowski, Marcin; Szczepkowski, Jacek; Witkowski, Marcin; Zawada, Michał; Gawlik, Wojciech (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Most of spinor condensates studied so far were produced in situ in dipole optical traps. Our new method allows production of spinor condensates in an expanding atomic cloud. Since the spinor condensate is created outside the trap, the Bose–Einstein condensate can be prepared in any trap, either magnetic or optical dipole, which significantly extends the experimental flexibility. The described method permits also study of collisions between low density spinor condensates.
Optica Applicata, Vol. 40, 2010, nr 3, s. 565-570
Keywords: optyka; spinor condensates; Bose–Einstein condensate